Investigating the dynamics of excitons in monolayer WSe2 before and after organic super acid treatment. Issue 19 (8th May 2018) - Chen, Xin; Wang, Zhuo; Wang, Lei; Wang, Hai-Yu; Yue, Yuan-Yuan; Wang, Hai; Wang, Xue-Peng; Wee, Andrew T. S.; Qiu, Cheng-Wei; Sun, Hong-Bo
Abstract : Exciton dynamics of monolayer WSe2 before and after organic super acid treatment investigated by broadband transient absorption spectroscopy. Abstract : Due to the large photoluminescence quantum yield, high mobility and good stability, organic super acid treated two-dimensional WSe2 has drawn much attention. However, reports about the influence of organic super acid treatment on the dynamic processes of excitons of monolayer WSe2 are still rare. In this work, through the broadband transient absorption spectra obtained using a femtosecond pump–probe system, we determine the dynamics of A′ and C excitons in monolayer and bulk WSe2 at room temperature. Besides this, we also observe the relaxation process of the holes between the two spin split states in the valence band maximum in organic super acid treated monolayer WSe2 . We find that the organic super acid treatment on monolayer WSe2 does not change the peak positions of the exciton states, while those bleaching peaks' intensities increase significantly due to the enhancement of oscillator strength for exciton states, corresponding to stronger steady-state photoluminescence. This could be attributed to the strain release induced by the defect repairing effect during the organic super acid treatment process.